2004
DOI: 10.1080/02699200410001703691
|View full text |Cite
|
Sign up to set email alerts
|

Articulatory placement for /t/, /d/, /k/ and /g/ targets in school age children with speech disorders associated with cleft palate

Abstract: This study used electropalatography (EPG) to identify place of articulation for lingual plosive targets /t/, /d/, /k/ and /g/ in the speech of 15 school age children with repaired cleft palate. Perceptual judgements indicated that all children had correct velar placement for /k/, /g/ targets, but /t/, /d/ targets were produced as errors involving palatalization or velar placement. An EPG classification scheme identified alveolar, palatal and velar placement. Articulations involving contact in alveolar and vela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 24 publications
0
8
0
2
Order By: Relevance
“…In Sell et al [7], palatalization and backing to uvular even range the second frequent consonant errors after dentalization/interdentalization [7]. Gibbon et al identified alveolar and uvular double articulations in /t/ and /d/ for children with cleft palate [65] and labial-lingual double articulations in few speakers with cleft palate as another form of compensatory speech disorder. The occurrence of misarticulations of Finnish dental consonants (/r/, /s/, and /l/) was reported to be maximal in children with a bilateral cleft lip and palate while children with just a cleft lip had the lowest number of misarticulations [40].…”
Section: Discussionmentioning
confidence: 96%
“…In Sell et al [7], palatalization and backing to uvular even range the second frequent consonant errors after dentalization/interdentalization [7]. Gibbon et al identified alveolar and uvular double articulations in /t/ and /d/ for children with cleft palate [65] and labial-lingual double articulations in few speakers with cleft palate as another form of compensatory speech disorder. The occurrence of misarticulations of Finnish dental consonants (/r/, /s/, and /l/) was reported to be maximal in children with a bilateral cleft lip and palate while children with just a cleft lip had the lowest number of misarticulations [40].…”
Section: Discussionmentioning
confidence: 96%
“…A hipernasalidade caracteriza-se por ressonância nasal de fones orais, causada pelo fechamento incompleto do esfíncter velofaríngeo 1,3,5,7,8 . Fonemas que necessitam de pressão intraoral para serem produzidos, como plosivos e fricativos, ocorrem com emissão nasal, também denominada escape aéreo nasal 1,5,9 . Na tentativa de impedir que a corrente aérea seja direcionada para o nariz pela falta de pressão intra-oral 8 , ocorrem movimentos compensatórios 1,3,6,7 , que acabam aumentando justamente o que tentam impedir.…”
Section: Rapid Maxillary Expansion With Haas and The Speech In Peopleunclassified
“…Children with repaired CLP are known to have difficulty producing lingual-alveolar articulations (Casal et al, 2002;Gibbon, 2004;Gibbon & Crampin, 2001;Gibbon, Ellis, & Crampin, 2004;Okazaki, Kato, & Onizuka, 1991;Santelmann, Sussman, & Chapman, 1999;Trost, 1981;Yamashita & Michi, 1991;Zajac, Cevidanes, Shah, & Haley, 2012). Using radiographic procedures, Trost (1981) identified middorsum palatal stops substituted for alveolar and velar stops by English speakers.…”
Section: Introductionmentioning
confidence: 97%